2022
DOI: 10.3390/ijms23063083
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System and Physical Activity—A Robust Duo in the Novel Therapeutic Approach against Metabolic Disorders

Abstract: Rapidly increasing worldwide prevalence of obesity and related pathologies encompassing coronary heart disease, hypertension, metabolic syndrome, or type 2 diabetes constitute serious threats to global health and are associated with a significantly elevated risk of premature death. Considering the enormous burden of these pathologies, novel therapeutic and preventive patterns are indispensable. Dysregulation of one of the most complex biological systems in the human body namely, the endocannabinoid system (ECS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 114 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…The specific and peculiar role of ECs in neuromuscular junctions gains great attention (Balezina et al., 2021; Behl et al., 2022; Dalle et al., 2022; Ge et al., 2020; Morsch et al., 2018; Tarasova, Khotkina, Gaydukov, et al., 2021) but still remains poorly studied up to date. Despite the relatively low density of CB1 receptors on muscle membranes, their activation by ECs plays a significant role in muscle metabolism and homeostasis (Alger, 2013; Charytoniuk et al., 2022; Dalle et al., 2022). This may be accompanied by the influence of ECs on nerve terminals to provide the release of important trophic factors, such as CGRP, to maintain and stabilize synaptic transmission and muscle contractions (Andersen & Clausen, 1993; Machado et al., 2019; Sala et al., 1995; Uchida et al., 1990; Takami et al., 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The specific and peculiar role of ECs in neuromuscular junctions gains great attention (Balezina et al., 2021; Behl et al., 2022; Dalle et al., 2022; Ge et al., 2020; Morsch et al., 2018; Tarasova, Khotkina, Gaydukov, et al., 2021) but still remains poorly studied up to date. Despite the relatively low density of CB1 receptors on muscle membranes, their activation by ECs plays a significant role in muscle metabolism and homeostasis (Alger, 2013; Charytoniuk et al., 2022; Dalle et al., 2022). This may be accompanied by the influence of ECs on nerve terminals to provide the release of important trophic factors, such as CGRP, to maintain and stabilize synaptic transmission and muscle contractions (Andersen & Clausen, 1993; Machado et al., 2019; Sala et al., 1995; Uchida et al., 1990; Takami et al., 1985).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the greater intensity of the dietary component (individual counseling visits and free provision of EVOO and mixed nuts) compared to the physical activity component (based on recommendations delivered by dietitians) of the Predimed-Plus study ( 39 ). Therefore, it is more likely that changes in eCBs and NAEs during the Predimed-Plus lifestyle intervention were due to the cardiometabolic effects of the MedDiet component than to those of the physical activity component, although some studies have already reported the modulation of eCBs by physical activity (mainly after acute exercise) ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…The two most studied eCBs are N-arachidonoylethanolamine (AEA) and arachidonoylglycerol (2-AG). AEA is a ligand for the CB1R while 2-AG is a ligand for both CB 1 and CB 2 receptors [49][50][51].…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…There are some studies that have investigated the influence of physical activity and/or exercise on the endocannabinoid signaling, though the mechanisms are still unclear. Physical activity depending on factors, such as type, frequency, intensity, duration, subject's age and gender can lead to the activation of the ECS, increasing the levels of AEA and 2-AG in the circulation and altering the levels of the CBRs [50,51]. The CBS activation positively affects many systems and tissues, including the central nervous system (e.g., anti-depressive properties, memory and mood improvement, increased neurogenesis and neuroplasticity), cardiovascular system (e.g., reduction in blood pressure, increased endothelial function), respiratory system (bronchodilation), digestive system (e.g., increase in insulin sensitivity, reduction in insulin resistance, reduction in leptin resistance), as well as the function of adipocytes (e.g., increased lipolysis, reduced lipogenesis and increase in adiponectin).…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%